Antipodes of “pink Christianity”: Konstantin Leontiev’s dispute with Fyodor Dostoyevsky and Lev Tolstoy - Broda, Marian (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
Konstantin Leontiev presented his religious views in a programmatic opposition to the so-called pink Christianity, found in the works and statements of Fyodor Dostoyevsky and Lev Tolstoy. Due to the central position of both his adversaries in the Russian literary, intellectual and cultural tradition, Leontiev’s dispute with them can be regarded as a polemic of a writer with a broadly understood communal tradition – not only with the Russian one, because in Dostoyevsky’s and Tolstoy’s thought Leontiev recognised symptomatic manifestations of much more general religious, cultural and social tendencies of his time. By unmasking the one-sidedness of the interpretation of Christianity that he criticised, he intended to restore the fullness of the Christian Truth. The huge heuristic potential of Leontiev’s perspective notwithstanding, it may be noticed that, in a sense, he himself became one of the victims of the “pink Christianity” which he combated – to the extent that he countered one interpretative one-sidedness with just another.